Workload-capacity imbalances and their impact on self-management complexity in patients with multimorbidity: a multicenter cross-sectional study - Binyu Zhao; Yujia Fu; Jingjie Wu; Erxu Xue; Chuyang Lai; Dandan Chen; Qiwei Wu; Jianing Yu; Qiaoyu Wu; Zhihong Ye; Jing Shao (Annals of Medicine)
Introduction Multimorbidity is increasing globally, emphasizing the need for effective self-management strategies. The Cumulative Complexity Model (CuCoM) offers a unique perspective on understanding self-management based on workload and capacity. This study aims to validate the CuCoM in multimorbid patients and identify tailored predictors of self-management.Methods This multicenter cross-sectional survey recruited 1920 multimorbid patients in five primary health centres and four hospitals in China. The questionnaire assessed workload (drug intake, doctor visits and follow-up, disruption in life, and health problems), capacity (social, environmental, financial, physical, and psychological), and self-management. Data were analyzed using latent profile analysis, chi-square, multivariate linear regression, and network analysis.Results d Patients were classified into four profiles: low workload-low capacity (10.2%), high workload-low capacity (7.5%), low workload-high capacity (64.6%), and high workload-high capacity (17.7%). Patients with low workload and high capacity exhibited better self-management (β = 0.271, p < 0.001), while those with high workload and low capacity exhibited poorer self-management (β=-0.187, p < 0.001). Social capacity was the strongest predictor for all profiles. Environmental capacity ranked second for ‘high workload-high capacity’ (R² = 3.26) and ‘low workload-low capacity’ (R² = 5.32) profiles. Financial capacity followed for the ‘low workload-high capacity’ profile (R² = 5.40), while psychological capacity was key in the ‘high workload-low capacity’ profile (R² = 6.40). In the network analysis, socioeconomic factors exhibited the central nodes (p < 0.05).Conclusions Personalized interventions designed to increase capacity and reduce workload are essential for improving self-management in multimorbid patients. Upstream policies promoting health equity are also crucial for better self-management outcomes.